Saberes ancestrales sobre métodos anticonceptivos en la población indígena de Yanalá, Ipiales 2024 - Serrano Gamboa, Emilce Yamileth (2024)
Family planning is a methodology that helps people have a full, healthy and safe sexual and reproductive life, through quality contraceptive services, respecting their rights and free decision. Therefore, the objective of this study was to develop educational strategies for the promotion of contraceptive methods with a sociocultural approach through quantitative research in the indigenous population of Yanalà Ipiales. This began with a diagnostic survey carried out on 52 people of childbearing age and it was found that 46% know that family planning is related to the decision to have children; 33% say that the spouse's decision is the main reason for not planning, 46% say that modern planning interferes with their cultural practices and beliefs, and 46% say that access to contraceptive methods is complicated by limited availability at health centers. With these results, the proposal was designed and implemented, which effectively educated people about the use of contraceptive methods from the perspective of sexual and reproductive health care and promoted healthy behaviors such as responsible and free decisions about how many children to have and when to have them. In conclusion, interculturality as a strategy made this convergence a fundamental and respectful resource to offer adequate health care as a mechanism for agreement, dialogue and exchange between ancestral and modern knowledge on reliable, informed and responsibly applicable family planning